Coatings and Thin-Film Technologies 2019
DOI: 10.5772/intechopen.79578
|View full text |Cite
|
Sign up to set email alerts
|

CdTe Thin Films: Deposition Techniques and Applications

Abstract: The II-IV semiconductor compound, CdTe, has suitable electrical and optical properties as photovoltaic and high-energy radiation sensor material. As an absorber material for thinfilm-based solar cells, CdTe holds the potentiality to fabricate high-efficiency solar cells by means of low-cost technologies. This chapter presents a comprehensive review on the CdTe thin-film deposition techniques as well as on the several configurations for the solar cell structures that have led the best efficiency conversion. Cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Spu ering is another common method for depositing thin films in thin-film solar cell fabrication. In spu ering, a target material (e.g., cadmium sulfide, indium tin oxide) is bombarded with highenergy ions in a vacuum chamber, causing atoms to be ejected and deposited onto a substrate [11]. Spu ering allows for the deposition of uniform and dense films over large areas, making it suitable for industrial-scale production of thin-film solar cells [12].…”
Section: Spu Eringmentioning
confidence: 99%
“…Spu ering is another common method for depositing thin films in thin-film solar cell fabrication. In spu ering, a target material (e.g., cadmium sulfide, indium tin oxide) is bombarded with highenergy ions in a vacuum chamber, causing atoms to be ejected and deposited onto a substrate [11]. Spu ering allows for the deposition of uniform and dense films over large areas, making it suitable for industrial-scale production of thin-film solar cells [12].…”
Section: Spu Eringmentioning
confidence: 99%
“…It has been reported that the thermal evaporated Au contact at room temperature has a work function (WF) in the range of 5.1-5.3 eV. [26][27][28] Additionally, CdTe has a WF of 5.7 eV, 29 which creates a high Schottky-barrier height in the range of 0.4-0.6 eV for the hole transport at the CdTe/Au interface. Therefore, the high barrier height impedes hole transport and causes the strong current limiting effect (i.e., roll over) in the light J-V characteristics, which leads to decreased V oc and device efficiency.…”
Section: Oxygen Varied Nio Films As Back Buffer Layer For Cdte Cellsmentioning
confidence: 99%
“…Two approaches were developed to deposit the absorber layer: (1) the vacuum-based deposition method and (2) the solution-based deposition approach. The vacuum-based deposition approach includes different techniques, such as sputtering, evaporation, and pulsed-laser deposition, while solution-based deposition involves developed techniques with high functionality, such as spin-coating, sol-gel, spray pyrolysis, chemical bath deposition, and screen-printing [28][29][30][31]. It is worth noting that the solution-based deposition approach offers great potential for simple fabrication and lowcost solar cells; however, it suffers from a lower stability compared to those fabricated by vacuum-based deposition approach [32,33].…”
Section: Heterojunction Thin-film Solar Cellsmentioning
confidence: 99%